The same ambiguous question was posted here
and I answered it as I understood it.
You did not respond at the time
http://www.jiskha.com/display.cgi?id=1271367239
Solve the equation.
log 6.44 + 3 log x - log x^2 = log 6.44 + 3
3 answers
I just noticed you changed it slightly
Now it becomes
3 log x - log x^2 = 3
log x^3 - log x^2 = 3
log (x^4/x^2) = 3
log x = 3
x = 10^3 = 1000
Now it becomes
3 log x - log x^2 = 3
log x^3 - log x^2 = 3
log (x^4/x^2) = 3
log x = 3
x = 10^3 = 1000
Thank you so much. I understand it now.